2020
DOI: 10.4103/jfmpc.jfmpc_356_20
|View full text |Cite
|
Sign up to set email alerts
|

Self-care practices among type II diabetics in rural area of Kancheepuram district, Tamil Nadu

Abstract: Introduction: Type 2 diabetes mellitus is one of the most prevalent noncommunicable diseases in India. The acute and chronic complications of diabetes impact the physical, mental, and social well-being of the patients, thereby, placing a major burden on the health care system. Studies have shown that adequate self-care practices among the patients will facilitate good glycemic control and prevent complications. Objectives: To study the patterns of self-care practice amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 19 publications
2
21
1
Order By: Relevance
“…The study is contradicted to the study conducted by Karthik RC, Radhakrishnan A, Vikram A, et al, (2020), cross sectional study on Self-care practices among type II diabetics in rural area of Kancheepuram district, Tamil Nadu. The result reveals that the overall prevalence of good self-care practices was very low (5.6%).…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…The study is contradicted to the study conducted by Karthik RC, Radhakrishnan A, Vikram A, et al, (2020), cross sectional study on Self-care practices among type II diabetics in rural area of Kancheepuram district, Tamil Nadu. The result reveals that the overall prevalence of good self-care practices was very low (5.6%).…”
Section: Discussioncontrasting
confidence: 71%
“…Moderate self-care practices were prevalent in 42% of the study participants whereas the majority (52.4%) of the study population had poor self-care practices regarding diabetes. [5] The study reveals that there is a moderate positive correlation between knowledge and practice scores where the value of r=0.430 which clearly infers that when the knowledge regarding diabetes among patients diagnosed with diabetes mellitus increases their practice level also increases…”
Section: Discussionmentioning
confidence: 77%
“…Results were similar to study conducted by Karthik et al out of 250 participants, 5.6% had good self-care, 42% had moderate self-care and 52% had very poor self-care. 10 In medication adherence, the outcome of the study revealed that out of total 150 samples majority 78% (117) participants had good adherence, 13.3% (20) participants had excellent adherence and only 8.6% ( 13) participants had poor level of adherence to medical regimen for diabetes mellitus. Srividya et al to assess adherence to medication among adults with diabetes mellitus of total 150 participants.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, patients in Butajiara and Addis Ababa (Ethiopia) have strictly adhered to their diabetes medicines (Habte et al, 2016). Medication adherence was also found to be high in quantitative (Chinnappan et al, 2020;Karthik et al, 2020;Uma Maheshwari et al, 2017) and qualitative (Selvaraj et al, 2016) studies done in India. However, in contrast to this study, in a quantitative study in southwest Ethiopia, medication adherence was low with poor self-care behaviors (Kassahun et al, 2016).…”
Section: Discussionmentioning
confidence: 97%